Hobbes: o Estado como produto do medo e da esperança - Costa, Judite Eugênia Barbosa (2012)
This work analizes the rising of the absolutist State, its causes and consequences, as well as its growing in the XVIIth England. We embase this work in the Thomas Hobes's political philosophy. He consideres that the State conception is linked to the might phenomenon. How is possible this conception in Hobbes? What bounds and functions has this might conception? To make explicit this conception, we'll take the historical context in which Hobbes developped your philosophical system. Following, we will analize human nature conception, nature laws, sovereignty and Civil State.